Correlating photovoltaic properties of a PTB7-Th:PC71BM blend to photophysics and microstructure as a function of thermal annealing. Issue 28 (3rd July 2017) - Krishnan Jagadamma, Lethy; Sajjad, Muhammad T.; Savikhin, Victoria; Toney, Michael F.; Samuel, Ifor D. W.
Abstract : The effect of thermal annealing on a polymer solar cell is investigated and related to changes in the photophysics and structure. Abstract : Selective optimisation of light harvesting materials and interface properties has brought breakthroughs in power conversion efficiency (11–12%) of organic photovoltaics (OPVs). However to translate this promising efficiency to economically viable applications, long term stability is a fundamental requirement. A number of degradation pathways, both extrinsic and intrinsic, reduce the long term stability of OPVs. Here, the photovoltaic properties of a highly efficient bulk heterojunction PTB7-Th:PC71 BM blend were investigated as a function of ex situ thermal annealing. The changes in charge generation, separation, and transport due to thermal annealing were measured and related to changes in the microstructure and photovoltaic performance. A 30% drop in the power conversion efficiency of PTB7-Th:PC71 BM blends upon thermal annealing at 150 °C was identified as mainly due to morphological instability induced by strong phase separation of donor and acceptor molecules of the blend films. Based on the insight gained from these investigations, enhanced thermal stability was demonstrated by replacing the PC71 BM fullerene acceptor with a non-fullerene acceptor ITIC, for which power conversion efficiency dropped only by 9% upon thermal annealing at 150 °C.